Pemberdayaan dan Pendampingan Masyarakat Pesisir Peduli Mangrove di Kawasan Mangrove Bangko-Bangko, Kabupaten Lombok Barat, Nusa Tenggara Barat - Firman Ali Rahman; Misdarti; Markum; Suyono; Reni Retnowathi; M. Barmawi; Hanapi; Wahyu Wijayanti; Alfian Pujian Hadi (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Empowering and assisting coastal communities who care about mangroves is one solution in maintaining sustainable coastal ecosystems. One of them is the Bangko-Bangko mangrove area which is vegetation that supports coastal forests. This service method is carried out through a process of mentoring and community empowerment. The results of the service show that it is important to empower and assist coastal communities adjacent to the Bangko-Bangko mangrove ecosystem in Sekotong District to maintain sustainable mangrove conservation. Apart from that, assistance from people who care about mangroves in the mangrove rehabilitation process is very necessary to ensure that the type of mangrove planted is appropriate to its habitat and growth zone so that the planting program can be successful with a high probability.